The Relationship between GPA and Prerequisite Courses on the Mastery of Simple Machines Concepts among Physics Education PLP Students at FKIP Untan - Irmayani, Ega Sri; Djudin, Tomo; Oktavianty, Erwina; Tiur, Haratua; Firdaus, Firdaus (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
This study aims to determine the effect of GPA and prerequisite courses simultaneously on the mastery of simple machine concepts in PLP II students at FKIP Untan Pontianak. This correlational study involved 50 seventh-semester students of the Physics education study program at the Faculty of Teacher Training and Education (FKIP) Pontianak, Tanjungpura University. Data collection was carried out using measurement techniques, namely tests. The achievement of prerequisite courses and microteaching competence of students were taken from the academic section of the faculty. The analysis found that GPA and prerequisite courses on mastery of simple machine teaching materials were significantly related to correlation coefficients (r = 0.38, r = 0.34, p < 0.05, respectively). In addition, the multiple correlation coefficient was also significant (R = 0.38, p < 0.05). This means that the relative contribution of the predictor variables of this study to the mastery of simple machine teaching materials is 15.1%, and the remaining 84.9% is determined by other factors not examined in this study. The study showed that GPA and prerequisite courses were significantly related to student's ability in the learning process.